Effect of Parboiling on Milling, Physicochemical, and Textural Properties of Medium‐ and Long‐Grain Germinated Brown Rice. Issue 1 (30th June 2015) - Han, Ashley; Jinn, Jia‐Rong; Mauromoustakos, Andy; Wang, Ya‐Jane
Abstract : Germinated brown rice is considered a more nutritious and palatable cooked product than conventional brown rice. However, germination usually decreases rice milling yield and alters some physicochemical properties. Parboiling is commonly used to increase milling yield and retain nutrients, but it also changes rice color and texture. The objective of this study was to investigate the effect of parboiling on milling, physicochemical, and textural properties of a medium‐grain and a long‐grain rice after germination at varying durations. Germinated rice samples of three germination durations were prepared with one germination time before the optimum time at which 70% of rice revealed hull protrusion, the optimum time, and one time after. Germinated rice was then immediately parboiled at 120°C for 20 min and was then immediately dried. The milling, physicochemical, and textural properties of parboiled germinated rice from both cultivars were determined. Parboiling significantly decreased the percentage of brokens, whiteness, and the apparent amylose content and increased γ‐aminobutyric acid content (GABA) in the nongerminated rice and rice at the first germination duration for both cultivars. Parboiling reduced pasting viscosities for both cultivars, but Jupiter still exhibited higher pasting viscosities than Wells. Cooked parboiled germinated rice was overall softer than nonparboiled rice because of kernel splitting, but Wells remained harder and less sticky than Jupiter. In conclusion, it is beneficial to combine parboiling with germination to enhance nutritional values and improve milling properties without affecting textural properties for both rice cultivars.